Hubungan antara Big Five Personality dengan Quarter Life Crisis pada Mahasiswa Tingkat Akhir di Universitas Negeri Padang - Fadila, Nurul; Dwatra, Free Dirga (Lembaga Yasin AlSys, 2024)
This study aims to see the relationship between big five personality and quarter life crisis in final year students at Padang State University. This research uses quantitative methods with a correlational research design. The sample collection technique in this study used cluster sampling technique. The number of respondents in this study was 116 final year students at Padang State University. The instrument in this study uses the scale of quarter life crisis crisis adopted from researcher Salsabilla (2023). And Goldberg's (1992) International Personality Item Pool-Big Five Factor Marker 50 (IPIP-BFM-50) scale, adapted to Indonesian by Akhtar & Azwar (2018). The results of the analysis used Product-Moment correlation analysis and found a significant negative relationship between the big five personality dimensions, namely extraversion, agreeableness, conscientiousness, neuroticism, and with quarter life crisis in final year students at Padang State University.